The Paradoxical Effect of the Documentary in Walter Salles’s Central do Brasil - Cynthia M. Tompkins (Studies in 20th & 21st Century Literature, 2009)
This article explores the fusion between the conventions of the documentary and fiction films in Walter Salles’s Central do Brasil (1998), tracing this synergy back to the impact of the documentary and Neorealism on the New Latin American Cinema and Cinema Novo, its Brazilian counterpart. After acknowledging Alberto Cavalcanti’s role in the development of British documentary and cinema in Brazil, this text examines Salles’s film in terms of Juliane Burton’s typology of the observational mode. Particular attention is given to Bill Nichols’s work on the textual conventions shared by the observational documentary and fiction films. The affective impact, which Nichols foregrounds, is reinforced by applying Gilles Deleuze’s views on the close-up. This article concludes by noting the intertextual reverberations between Central do Brasil and Cinema Novo, a phenomenon typical of the mid-1990’s revival of Brazilian cinema, which would come to be defined as Cinema da Retomada.
Keywords: Walter Salles; Central do Brasil; Neorealism; New Latin American Cinema; Cinema Novo; Brazil; Brazilian; Alberto Cavalcanti; British Documentary; observational mode; close-up; Gilles Deleuze; mid-1990’s; Brazilian cinema; Cinema da Retomada